Job-hopping in Silicon Valley: some evidence concerning the micro-foundations of a high technology cluster - Bruce Fallick; Charles A. Fleischman; James B. Rebitzer (Levy Economics Institute of Bard College, 2005)
Observers of Silicon Valley's computer cluster report that employees move rapidly between competing firms, but evidence supporting this claim is scarce. Job-hopping is important in computer clusters because it facilitates the reallocation of talent and resources toward firms with superior innovations. Using new data on labor mobility, we find higher rates of job-hopping for college-educated men in Silicon Valley's computer industry than in computer clusters located out of the state. Mobility rates in other California computer clusters are similar to Silicon Valley's, suggesting some role for features of California law that make non-compete agreements unenforceable. Consistent with our model of innovation, mobility rates outside of computer industries are no higher in California than elsewhere.
Keywords: R12; L63; O3; J63; J48; 330; agglomerations; clusters; non-compete agreements; human capital; innovation; Silicon Valley; modular production; Arbeitsmobilität; Regionale Konzentration; Externer Effekt; Humankapital; Computerindustrie; Kalifornien